Gerenciamento da fila de espera para cirurgia ginecológica em hospital municipal da Zona Sul de São Paulo: como garantir acesso e otimizar a utilização de recursos - Barbosa, Mariana Granado (2018)
Waiting lists are a chronic problem in countries that opted for universal health systems. However, there are few studies on waiting lists in health services in Brazil. This case study aims to contribute by adding metrics to this discussion and grounding it around the economic-financial viability of health care decisions and access regulation in a broader way. Starting from the context of a municipal hospital in the south of the city of São Paulo, we analyzed two different scenarios: the demand for primary care for consultation with a specialist, which does not always end with the recommendation of surgery, and inpatient waiting lists, which have patients that were already evaluated and are waiting for the surgery. From this data analysis, we draw a new management model of gynaecologic elective surgery waiting list in this hospital. Our proposal does not aim to achieve zero wait, nor is it based on a single strategy. Our main conclusion is that the most efficient strategy for the waiting lists management involves the strengthening of health care networks’ integration actions. In the Unified Health System it can effectively enable the delivery of greater value in the assistance provided and can be done through local initiatives.